PRECEPTORS’ ROLE MODELLING OF SENIOR B.Sc.N. STUDENTS EXPLORED THROUGH REFLECTIONS OF FACULTY - Cavalieri, Vanessa E. (My University, 2013)
Preceptorship is an experiential learning approach whereby a senior B.Sc.N. student, a direct care Registered Nurse (preceptor), and a faculty member collaborate to successfully facilitate a students’ learning in a clinical course. Preceptors act as both clinical teachers and professional role models to students. Role modelling can be a powerful experiential teaching-learning strategy. The objective of this cross-sectional survey was to examine students’ viewpoints about role modelling by their preceptors during senior clinical courses, as viewed through faculty members’ reflections. A conceptualization of preceptors as stage role models was developed, providing a unique perspective that includes role modelling typology, re-examination of “negative” role modelling, and intentionality. Data were collected and analyzed using Q-methodology procedures. By-person factor analysis revealed that students’ priorities for role modelling by preceptors vary. Four distinct student viewpoints emerged: the importance of explicit teaching (Factor 1), the significance of socialization behaviours (Factor 2), the foundations of practice knowledge and skills (Factor 3), and the pivotal role of preceptor authenticity (Factor 4). The findings also highlighted the importance of harnessing role modelling as an intentional teaching-learning strategy, including use of critical reflection on the part of the role model and the learner, and being explicit about what is being role modelled. Implications for education, clinical practice, and future research are discussed.
Keywords: role modelling; preceptor; experiential learning; clinical teaching; Q-methodology; Nursing; Nursing